The novel 5-lipoxygenase inhibitor ABT-761 attenuates cerebral vasospasm in a rabbit model of subarachnoid hemorrhage - Barbosa, MD (2001)
OBJECTIVE: Eicosanoids have been implicated in the pathogenesis of cerebral vasospasm after subarachnoid hemorrhage (SAH). Leukotrienes, 5-hydroxyperoxyeicosatetraenoic acid, and 5-hydroxyeicosatetraenoic acid are part of this group of substances, resulting from the 5-lipoxygenase activity on arachidonic acid metabolism. This study examined the effects of ABT-761, a new 5-lipoxygenase inhibitor, on cerebral vasospasm in an in vivo rabbit model of SAH. METHODS: A total of 48 rabbits were assigned to one of six groups: SAH + placebo (n = 8), SAH + ABT-761 20 mg/kg (n = 8), SAH + ABT-761 30 mg/kg (n = 8), control + placebo (n = 8), control + ABT-761 20 mg/kg (n = 8), and control + ABT-761 30 mg/kg (n = 8). Drug administration was initiated 30 minutes after induction of SAH and repeated 24 hours later. The animals were killed 48 hours after SAH, using the perfusion-fixation method. The cross sectional areas of basilar artery histological sections were measured by an investigator blinded to the treatment groups of the individual samples. RESULTS: In placebo-treated animals, the average luminal cross sectional area of the basilar artery was reduced by 68% after SAH as compared with controls (P < 0.0001). After SAH, the vasospastic response was attenuated in animals treated with 20 or 30 mg/kg representing a 28 or 35% reduction, respectively (P = 0.0011 and P = 0.0038). CONCLUSION: The results demonstrated that ABT-761 is effective in attenuating experimental cerebral vasospasm, indicating that this new drug represents a potential therapeutic agent for the treatment of vasospasm after SAH.